Giardia spp. and the Gut Microbiota: Dangerous Liaisons - Fekete, Elena; Allain, Thibault; Siddiq, Affan; Sosnowski, Olivia; Buret, Andre G. (Frontiers in Microbiology, 2021)
Alteration of the intestinal microbiome by enteropathogens is commonly associated with gastrointestinal diseases and disorders, and has far-reaching consequences for overall health. Significant advances have been made in understanding the role of microbial dysbiosis during intestinal infections, including infection with the protozoan parasite Giardia duodenalis, one of the most prevalent gut protozoan. Altered species composition and diversity, functional changes in the commensal microbiota, and changes to intestinal bacterial biofilm structure have all been demonstrated during the course of Giardia infection, and have been implicated in Giardia pathogenesis. Conversely, the gut microbiota has been found to regulate parasite colonization and establishment, and plays a critical role in immune modulation during mono and polymicrobial infections. These disruptions to the commensal microbiome may contribute to a number of acute, chronic, and post-infectious clinical manifestations of giardiasis, and may account for variations in disease presentation within and between infected populations. This review discusses recent advances in characterizing Giardia-induced bacterial dysbiosis in the gut, and the roles of dysbiosis in Giardia pathogenesis.